Global Investment in Renewable Energy: Evolutions and Challenges Brought by Covid-19 Crisis - Andreea-Emanuela DRĂGOI; Paul CALANTER (Communications of International Proceedings, 2020)
Investments in renewable energy are considered a major objective of sustainable economic development all over the world as they are a driver of technological progress and a cornerstone in combating climate change. Our paper aims to present the progress made on investments in renewable energy globally, but also to highlight, through a comparative quantitative analysis, the impact of the COVID-19 crisis in the field. The research methodology is based both on a screening of the most relevant global reports, but also on the use of case studies presenting progress and challenges in two of the most advanced economies: US and China, given that prior to the COVID-19 crisis both states had ambitious targets for the development of renewable energy. The concluding part of the paper will present whether the pandemic crisis and its economic impact are an impediment to investments in renewable energy or may bring some opportunities for the future of these clean energy.
Keywords: Institute for World Economy; Romanian Academy; Bucharest; Romania